Notch-Mediated Epigenetic Regulation of Voltage-Gated Potassium Currents. Issue 12 (9th December 2016) - Khandekar, Aditi; Springer, Steven; Wang, Wei; Hicks, Stephanie; Weinheimer, Carla; Diaz-Trelles, Ramon; Nerbonne, Jeanne M.; Rentschler, Stacey
Abstract : Rationale: : Ventricular arrhythmias often arise from the Purkinje–myocyte junction and are a leading cause of sudden cardiac death. Notch activation reprograms cardiac myocytes to an induced Purkinje-like state characterized by prolonged action potential duration and expression of Purkinje-enriched genes. Objective: : To understand the mechanism by which canonical Notch signaling causes action potential prolongation. Methods and Results: : We find that endogenous Purkinje cells have reduced peak K + current, Ito, and IK, slow when compared with ventricular myocytes. Consistent with partial reprogramming toward a Purkinje-like phenotype, Notch activation decreases peak outward K + current density, as well as the outward K + current components Ito, f and IK, slow . Gene expression studies in Notch-activated ventricles demonstrate upregulation of Purkinje-enriched genes Contactin-2 and Scn5a and downregulation of K + channel subunit genes that contribute to Ito, f and IK, slow . In contrast, inactivation of Notch signaling results in increased cell size commensurate with increased K + current amplitudes and mimics physiological hypertrophy. Notch-induced changes in K + current density are regulated at least in part via transcriptional changes. Chromatin immunoprecipitation demonstrates dynamic RBP-J (recombination signal binding protein for immunoglobulin kappa J region) binding and loss of active histone marks on K + channel subunit promoters with Notch activation, and similar transcriptional and epigenetic changes occur in a heart failure model. Interestingly, there is a differential response in Notch target gene expression and cellular electrophysiology in left versus right ventricular cardiac myocytes. Conclusions: : In summary, these findings demonstrate a novel mechanism for regulation of voltage-gated potassium currents in the setting of cardiac pathology and may provide a novel target for arrhythmia drug design. Abstract : Supplemental Digital Content is available in the text.